Foaming agent, method for actively lubricating hob by using foaming agent and method for testing performance of hob by using foaming agent

By using a foaming agent including foaming agent, foam stabilizing agent, thickening agent and solvent in the excavation of full-section rock tunnels, combined with the active lubrication hob method, the relative friction coefficient of the knife rock is controlled, and the problem of serious wear failure of the knife ring is solved, and the effect of reducing wear rate and extending wear life is achieved.

CN119662225APending Publication Date: 2025-03-21XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722922.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the excavation process of full-section rock tunnels, the knife ring is prone to bias, string grinding, and normal wear failure, resulting in high maintenance costs and serious wear and failure of the hob under extreme excavation rock layers, affecting the success or failure of the tunnel boring project.

Method used

A foaming agent including a foaming agent, a foam stabilizing agent, a thickening agent and a solvent is used. By spraying the foaming agent on the palm surface, combined with an active lubrication hob method, the relative friction coefficient of the knife rock is controlled, the abrasiveness of the compact core is reduced, and the friction and wear life of the knife ring is improved.

Benefits of technology

It effectively reduces the wear rate of the knife ring, extends the wear life, improves the rock breaking efficiency, and the foaming agent is environmentally friendly, easy to degrade, does not pollute the environment or damage the main structure of the knife plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662225A_ABST
    Figure CN119662225A_ABST
Patent Text Reader

Abstract

The invention provides a foaming agent and an active hob lubricating method and a performance testing method thereof, the foaming agent comprises an original solution, and the foaming agent is characterized in that basic components of the original solution comprise a foaming agent, a foam stabilizer, a thickening agent and a solvent; for the medium-hardness rock stratum, the original solution further comprises an acidifying agent; aiming at the existence of a rock stratum rich hard water medium, the original solution component further comprises a chelating agent; aiming at serious friction of the hob on the interface of the cutter and the rock, the original solution also comprises a lubricant. The method for actively lubricating the hobbing cutter is characterized in that the foaming agent is sprayed to a tunnel face through a spraying opening formed in a cutter head. The performance testing method suitable for the foaming agent is characterized by comprising basic performance testing of an original solution, stability testing of the original solution and mass difference measurement of a cutter ring sample in the process of a cutter rock abrasion test. The friction wear life of the cutter ring can be prolonged by reducing the abrasiveness of dense nuclear substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tunnel excavation, and in particular to a foaming agent and an active lubrication method for a roller cutter thereof and a performance testing method thereof. Background Art

[0002] The full-face rock tunnel boring machine (TBM) uses the cutter ring part of the disc cutter (cutter) installed on the cutterhead to cut the rock. Under the thrust of the cutterhead, the cutter ring vertically penetrates the rock of the tunnel face to a certain depth; at the same time, driven by the torque of the cutterhead, the cutter ring continuously crushes the rock by rotating and rolling. Engineering construction experience shows that the cutter ring is prone to wear failure behaviors such as eccentric wear, chord wear, and normal wear failure (equal radial wear, and the radial wear exceeds the threshold). The maintenance cost caused by such failure behaviors accounts for about 30% of the total cost of tunnel excavation construction. Under extreme excavation rock formations such as "three highs" (high confining pressure, high strength, and high quartz content), the wear failure of the cutter will be more serious, and its tool loss cost even determines the success or failure of the tunnel excavation project. Because the cutter ring is easily worn and consumed, there was once a saying in the industry that "iron is exchanged for stone." Although the academic community has conducted extensive research on the rock-breaking mechanism of roller cutters, optimal design of cutterhead tools, and remanufacturing and repair of cutter rings, due to the constraints of current material science and processing and preparation technology, the above research has had little effect on improving the wear life of roller cutters.

[0003] During the rock-breaking process of the disc cutter, the unique interaction mechanism between the cutter and the rock determines that the disc cutter ring has a high friction wear rate. Specifically, during the penetration of the disc cutter ring into the rock, the cracks and holes in the local rock at the bottom of the disc cutter ring are first compacted by the extrusion stress of the cutter, and then the rock mass undergoes a short elastic-plastic deformation stage; when the extrusion stress reaches the compressive strength of the rock, the rock is extruded and destroyed, and a small amount of small-sized rock slag is produced; due to the restriction of the original rock and the cutting edge of the disc cutter ring, the rock slag is further squeezed into rock powder, and then a dense core material (hereinafter referred to as dense core) with a certain bonding strength and composed of fine rock powder is formed; research shows that the stress level in the dense core area is much higher than the uniaxial compressive strength of the rock, which also determines that the contact stress level of the cutter rock is much higher than the traditional level (see "Study of pressure distribution within the crushed zone in the contact area between rock and disc cutters" International Journal of Rock Mechanics & Mining Sciences, Issue 57). In addition, the dense core is composed of densified rock powder with sharp edges (similar to a grinding wheel with consolidation of corundum), and acts as an abrasive material on the interface between the cutter and rock, so its abrasiveness is far greater than that of the original rock and loose rock powder. Theoretically, by using pre-grooving, rock breaking on the open surface, and local rock pre-irradiation weakening techniques to inhibit the development of the dense core at the bottom of the blade during the cutter penetration process, the friction and wear rate of the cutter ring can be reduced from two aspects: the contact stress level between the cutter and the rock and the abrasiveness of the dense core; but the problem is that simply inhibiting the development of the dense core will reduce the stress level of the dense core area, thereby affecting the length of the lateral cracks derived from the dense core area, and ultimately affecting the derivative intersection of the lateral cracks between adjacent cutters when the cutter ring rolls and breaks the rock (large rock fragments that penetrate adjacent cutters will be produced), resulting in low rock crushing efficiency. It can be seen that when the cutter breaks the rock, in order to accumulate energy sufficient to drive the lateral cracks between adjacent cutters to derive and converge, the cutter must penetrate the rock to a certain depth (i.e., cutting depth) so that the stress level accumulation in the dense core area reaches a certain level; and the process of the cutter ring penetrating into the rock inevitably introduces the phenomenon of dense core derivation and development; this phenomenon inevitably leads to high cutter-rock contact stress level and high abrasiveness of the dense core, making it difficult to break through the bottleneck problem of the wear life of the cutter in the short term.It should be emphasized that the existing lubrication technology used in the mechanical field is not applicable to this field for the following reasons: 1) The lubrication cost is high and pollutes the environment; some of it may damage the main structure of the cutter disc; 2) This lubrication method is mainly based on the interaction mechanism between metal components, which is completely different from the aforementioned knife-rock interaction mechanism; therefore, if it is blindly applied, it will seriously reduce the knife-rock friction coefficient and greatly increase the slip rate of the cutter ring, causing the cutter ring wear rate to increase instead of decrease, and at the same time reduce the rock breaking efficiency; 3) The index system of lubrication performance and its performance detection method are completely different, so it is not suitable for densified rock powder with sharp edges.

[0004] How to effectively reduce the abrasiveness of the dense core material to increase the friction and wear life of the cutter ring while ensuring that the dense core is fully derived and developed (that is, ensuring that the efficiency of the cutter rock breaking is not reduced), without increasing the slip rate of the cutter ring (that is, ensuring that the cutter ring breaks rock in the form of a pure cutter as much as possible), and without polluting the environment and damaging the main structure of the cutter disc is an urgent problem to be solved by researchers in this field. Summary of the invention

[0005] In view of the serious problem of cutter ring wear failure during TBM excavation, the present invention proposes a foaming agent to improve the friction and wear life of the cutter ring under the premise of ensuring that the dense core is fully derived and developed, not increasing the slip rate of the cutter ring, not polluting the environment, and not damaging the main structure of the cutter head, which is characterized by:

[0006] Includes the original solution;

[0007] The components and mass fractions of the original solution are as follows:

[0008] Foaming agent: sodium lauryl ether sulfate sulfonic acid is used as the foaming agent; the mass fraction of the foaming agent is 15-32%;

[0009] Foam stabilizer: silicone resin polyether emulsion is used as the foam stabilizer; the mass fraction of the foam stabilizer is 2%;

[0010] Thickener: guar gum is used as the thickener; the mass fraction of the thickener is 0.1-0.5%;

[0011] Solvent: Deionized water was used as the solvent.

[0012] Preferably, the foam stabilizer is prepared by mixing silicone polyether emulsion and dodecyl dimethyl amine oxide; the mass fractions of silicone polyether emulsion and dodecyl dimethyl amine oxide are both 2%.

[0013] Preferably, the components of the original solution also include a chelating agent: Cublen-K2523 is used as the chelating agent, and its mass fraction is 1-1.5%.

[0014] Preferably, the original solution also includes a lubricant: polyethylene oxide is used as the lubricant, and its mass fraction is 0.1-6%.

[0015] Preferably, an acidulant is also included; the acidulant is used to acidify the original solution to obtain an acidified solution.

[0016] More preferably, oxalic acid is used as the acidulant;

[0017] More preferably, the pH value of the acidified solution is 5.

[0018] The active lubrication method for a roller cutter used in combination with a foaming agent of the present invention is characterized in that the foaming agent is sprayed onto the tunnel face through a spraying port arranged on the cutter disc.

[0019] A performance testing method used in conjunction with a foaming agent of the present invention is characterized by comprising the following steps:

[0020] S1: Prepare the original solution according to the geological conditions of the rock formation where the TBM is located;

[0021] S2: Conduct basic performance tests on the original solution, including the following steps:

[0022] S2-1: Calculate the foaming expansion ratio FER (%) according to formula (1);

[0023] FER=V f / V t ×100% (1)

[0024] Where V f V is the foaming volume; t is the volume of the original solution;

[0025] S2-2: Calculate the defoaming rate F of the original solution according to formula (2) s The time t1 (min) taken to reach 50% is the foam half-life;

[0026] F s =(M s / M0)×100% (2)

[0027] Where M s is the mass of the dissipated bubble; M0 is the initial mass of the bubble;

[0028] S2-3: Carry out foam morphology and quality observation;

[0029] S3: Conduct stability test of the original solution, including the following steps:

[0030] S3-1 Pressure resistance test: A pressure load F is applied to the original solution prepared in S1 by means of a loading piston; the pressure load F is calculated and determined using formula (3):

[0031] F=πr 2 P0 (3)

[0032] Where r is the radius of the loading piston; P0 is the stress level in the knife-rock contact area, which is given by the following formula (4):

[0033]

[0034] Where C is the dimensionless coefficient; R is the radius of the hob; σ c is the uniaxial compressive strength of rock; t is the tensile strength of the rock; T is the blade width of the roller cutter; S is the distance between the cutters; is the contact angle between the cutter and the rock, given by:

[0035]

[0036] Where H is the actual penetration depth of the hob in the project;

[0037] According to formula (6), the liquid precipitation ratio LPR (%) of the original solution from the initial moment to the static time T2 is measured; T2 is the time required for the original solution to completely precipitate;

[0038] LPR=(V s / V0)×100% (6)

[0039] Where V s is the volume of liquid released due to foam bursting at time T2; V0 is the total liquid volume after the foam completely dissipates;

[0040] The foam half-life of the original solution under different pressure loads F is measured according to formula (7); in addition, the half-life decrease under the pressure load F is calculated;

[0041] S3-2 Acid, alkali and salt resistance test: prepare acid resistance test solution, alkali resistance test solution and salt resistance test solution; carry out basic performance test of the test solution; immerse the corrosion resistance test sample with the same material as the knife ring in the test solution, carry out electrochemical corrosion degree test, and measure the corrosion rate of the corrosion resistance test sample;

[0042] S4: Conduct a grinding test of a cutter ring sample and a rock sample soaked in a foaming agent according to the present invention, and measure the mass difference of the cutter ring sample before and after the grinding test.

[0043] Preferably, the electrochemical corrosion degree test is performed in the following steps:

[0044] S3-2-1: Grind and polish a block sample with the same material as the knife ring, ultrasonically clean the block sample with ethanol and deionized water, and then dry it to prepare a corrosion resistance test sample;

[0045] S3-2-2: Completely immerse the corrosion resistance test sample in the test solution;

[0046] S3-2-3: When the immersion time is T3: measure the open circuit potential of the corrosion test sample; perform electrochemical impedance spectroscopy analysis on the corrosion test sample through an electrochemical workstation to obtain the impedance data of the corrosion test sample in the test solution; obtain the corrosion current density and corrosion potential through anodic and cathodic polarization curve tests;

[0047] S3-2-4: Use formula (7) to calculate the corrosion rate v′ of the corrosion resistance test sample under different test conditions:

[0048]

[0049] Where: Δm is the mass difference of the corrosion test sample before and after immersion; A is the surface area of ​​the corrosion test sample.

[0050] Preferably, S4 comprises the following steps:

[0051] S4-1: soaking the rock sample in a foaming agent of the present invention;

[0052] S4-2: Conduct a grinding test between the cutter ring sample and the rock sample; during the grinding test: use a three-axis force sensor to collect the vertical cutting load of the cutter ring sample in real time; use a high-speed camera to record the knife-rock grinding process; use an infrared thermal imager to record the temperature field distribution on the surface of the cutter ring sample and the rock sample;

[0053] S4-3: When the grinding distance is L: weigh the mass difference of the cutter ring sample before and after the grinding test, and the mass difference of the rock sample; observe and record the surface profiles of the cutter ring sample and the rock sample; calculate the slip rate of the cutter ring sample;

[0054] More preferably, in S4-2: the test penetration depth h of the cutter ring specimen should be determined based on the similarity principle of stress level P0 in the cutter-rock contact area. x ; The linear cutting speed v of the cutter ring sample should be determined based on the principle of similar linear speed levels of the roller cutter breaking rock.

[0055] The benefits of the present invention are as follows: the foaming agent of the present invention is environmentally friendly, each component is easily degraded, and can inhibit oxygen absorption corrosion of steel materials such as cutter rings; when the acidifier and the pH value of the acidified solution are reasonably selected, the corrosion rate of the foaming agent of the present invention on steel materials such as cutter rings is much lower than the wear failure rate of the hob; by reasonably setting different components, the construction requirements of deep extremely hard rock formations, water-rich rock formations, quartzite and other highly abrasive rock formations can be met; the basic performance, pressure resistance and acid, alkali and salt resistance of the foaming agent of the present invention are all good, which means that the generated foam can resist the stress level of the knife-rock contact area and can adapt to the water storage in ordinary rock formations. Acidic, alkaline and saline environments under medium conditions; by spraying a foaming agent of the present invention on the entire face, the cutter ring sample can be placed under wet cutting conditions, effectively reducing the surface temperature of the tool; most importantly, the present invention not only improves the excavation of rock and the rock breaking efficiency of the roller by chemically reacting acid molecules with mineral components in the rock, but also reduces the high abrasiveness of the dense core through passivation, avoids the sharp edges of rock powder from scratching and damaging the cutter ring surface through the isolation and protection of the liquid film, and prevents the cutter ring slip rate from fluctuating significantly after the application of the present invention by regulating the relative friction coefficient of the cutter rock, thereby fundamentally reducing the cutter ring wear rate.

[0056] In addition, the present invention designs a test method for the foaming agent used for active lubrication of the roller cutter, which meets the geological requirements of the working conditions faced by the TBM when excavating the rock formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The present invention is a performance test flow chart of a foaming agent.

[0058] Figure 2 This is the schematic diagram of the pressure resistance test of the original solution.

[0059] Figure 3 A schematic diagram of an active lubrication rolling cutter method used in conjunction with a foaming agent of the present invention.

[0060] Figure 4 This is the test result diagram of the liquid separation ratio of the original solution under different pressure loads.

[0061] Figure 5 The graph shows the test results of the half-life of the original solution and its decrease under different pressure loads.

[0062] Figure 6 This is a graph showing the basic performance test results of the original solution in different acidic pH ranges.

[0063] Figure 7 This is the measured mass and mass difference diagram of H13 steel samples after being immersed in acidified solution (using oxalic acid as acidifier) ​​(including the control group immersed in deionized water).

[0064] Figure 8 The graph shows the measured hardness and hardness reduction data of H13 steel samples before and after immersion in an acidified solution (using oxalic acid as the acidifier) ​​(including the control group immersed in deionized water).

[0065] Fig. 9 The graph shows the mean and increase data of the friction coefficient on the surface of rock samples after being immersed in acidizing solutions using oxalic acid and citric acid as acidifiers, respectively.

[0066] Fig.10 This is the schematic diagram of the knife-rock grinding test device.

[0067] Fig.11 This is the position relationship diagram between the cutter ring sample and the rock sample at the beginning of the cutter-rock grinding test.

[0068] Fig.12 This is the flow chart of the knife-rock grinding test.

[0069] Fig.13 These are the theoretical slip rate and measured slip rate of the cutter ring sample when the rock sample is in dry condition (dry cutting condition) and immersed in deionized water, original solution and acidified solution.

[0070] Fig.14 is the mass difference Δm of the cutter ring sample before and after the grinding test when the rock is in dry condition, and immersed in deionized water, original solution and acidified solution.

[0071] Fig.15 The mean depth and width of the groove produced by the cutter ring sample on the rock sample after the knife-rock grinding test when the rock is in dry condition and immersed in deionized water, original solution and acidified solution respectively.

[0072] Fig.16 The curves are as follows: the mean vertical cutting load on the cutter ring specimen varies with time intervals in the cutter-rock grinding test when the rock is dry, immersed in deionized water, original solution and acidified solution, respectively.

[0073] Fig.17 This is a schematic diagram of the mechanism of influence of a foaming agent on knife rock during immersion in the present invention. DETAILED DESCRIPTION

[0074] In order to clearly illustrate the purpose, technical scheme and advantages of the present invention, the technical scheme of the present invention is described in detail below, but the described embodiments are only part of the embodiments of the present invention, not all examples. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The technical scheme of the present invention is further described in detail below through the drawings and embodiments.

[0075] Aiming at the serious problem of cutter ring wear failure during TBM excavation, the present invention proposes a foaming agent to improve the friction and wear life of the cutter ring under the premise of ensuring that the dense core is fully derived and developed, not increasing the slip rate of the cutter ring, not polluting the environment, and not corroding and damaging the main structure of the cutter head, which is characterized by: comprising an original solution;

[0076] The components and mass fractions of the original solution are as follows:

[0077] Foaming agent: sodium lauryl ether sulfate sulfonic acid is used as the foaming agent; studies have shown that the foaming agent is an anionic surfactant, has relatively good foaming effect, is easily soluble in water, is easily degraded by the secretions of γ-proteobacteria, and has good cleaning, emulsification and foaming properties; the mass fraction of the foaming agent is 15-32%;

[0078] Foam stabilizer: Considering the high contact stress level of the knife-rock contact interface, silicone resin polyether emulsion is used as a foam stabilizer to significantly improve the stability of the foam, make the foam more durable, enhance the mechanical strength and elasticity of the liquid film, and thus prevent the foam from breaking under the action of external force; the mass fraction of the foam stabilizer is 2%;

[0079] Thickener: guar gum is used as a thickener to increase the viscosity of the foam, improve the fineness of the foam, and make the foam more uniform and fine; at the same time, it is used to enhance the compatibility of the foam with the medium, so that the foam can better adhere to the contact surface of the knife rock and is not easy to fall off; the mass fraction of the thickener is 0.1-0.5%;

[0080] Solvent: Deionized water was used as the solvent.

[0081] Taking into account the higher contact stress level of the knife-rock contact interface under deep extremely hard rock formations, it is preferred to use silicone resin polyether emulsion and dodecyl dimethyl amine oxide to mix and prepare a foam stabilizer; studies have shown that silicone resin polyether emulsion and dodecyl dimethyl amine oxide regulate the stability of the liquid film structure from two levels: surfactant molecules and groups; the mass fractions of silicone resin polyether emulsion and dodecyl dimethyl amine oxide are both 2%.

[0082] TBM has a certain probability of being in a water-rich rock formation. At this time, the groundwater medium, especially the hard water medium, will cause the foaming agent to aggregate and precipitate, reducing the foaming effect. In order to maximize the foaming effect, as a preferred embodiment, the components of the original solution also include a chelating agent: the mass fraction of the chelating agent is 1-1.5%.

[0083] More preferably, Cublen-K2523 is used as a chelating agent; studies have shown that this component can effectively reduce the risk of polymerization and precipitation of the foaming agent caused by hard water media in the rock formation environment.

[0084] Considering that when TBM is in a highly abrasive rock formation such as quartzite, the quartz mineral component will further increase the friction coefficient of the cutter-rock contact interface, thereby increasing the abrasiveness of the dense core. Therefore, in order to reasonably reduce the friction coefficient of the roller cutter relative to the rock, as a preferred method, the original solution also includes a lubricant: polyethylene oxide is used as a lubricant, and its mass fraction is 0.1-6%. Studies have shown that this component has good lubrication properties and chemical inertness.

[0085] It has been measured that the pH value of the original solution of the present invention is about 7.4. For extremely difficult-to-dig rock formations such as the three highs (high confining pressure, high strength, and high quartz content), in order to weaken the rock strength before the roller cutter rolls and breaks the rock, it is more preferred that a foaming agent of the present invention also includes an acidifier and a neutralizer; the acidifier and the neutralizer are used to adjust the pH value of the original solution to 4-6, that is, on the basis of the original solution, an acidified solution is further obtained by an acidification method. In this example, more specifically, inorganic acids such as HCl and sulfuric acid, or organic acids such as oxalic acid and citric acid can be used as acidifiers; and NaOH is used as an alkaline neutralizer. Studies have shown that after being soaked in an acidified solution, the mineral components in the rock will undergo a series of chemical reactions as shown in Table 1; this destroys the integrity of the rock, reduces the compressive strength of the rock, and improves the digging ability of the rock.

[0086] Table 1 Main chemical reactions of mineral components in rocks after being immersed in acidified solution

[0087]

[0088]

[0089] In order to evaluate the influence of the acidified solutions obtained by acidification with different acidifiers on the typical knife ring material, the measured mass and its change (mass difference), measured hardness and its decrease of H13 steel specimens (representing the common material of knife ring) after being immersed in different acidified solutions (including the control group immersed in deionized water) were tested. Figure 7 and Figure 8The data are obtained from actual measurements when oxalic acid is used as an acidifying agent. In the above two figures, OA3-6 represent acidified solutions in which the pH value of the original solution is adjusted to 3, 4, 5, and 6 using oxalic acid solution. Studies have shown that under the same pH value of the acidified solution, the corrosion rate of the H13 steel sample obtained by acidification with citric acid is higher than that obtained by acidification with oxalic acid; compared with other inorganic acids, the corrosion rate of the knife ring material and the weakening effect of the surface hardness of oxalic acid are relatively low. In addition, considering that organic acids also have the advantages of strong degradability and being more environmentally friendly, oxalic acid is preferably selected as the acidifying agent.

[0090] The experiment of immersing H13 steel samples in acidified solutions with different pH values ​​was carried out. When the immersion time reached 5h, it was found that when the acidity was strong, the corrosion rate of H13 steel samples was slightly higher than the 1.5g / (m 2 ·h), which is equivalent to pickling the surface of the H13 steel sample, removing the oxide layer on the surface of the sample, but not corroding the base layer of the H13 steel sample; taking the hob with the smallest cumulative wear of a certain model of TBM for calculation, it is found that its wear rate is about 30g / (m 2 ·h), which is much higher than the corrosion rate of the cutter ring material by the acid solution. It can be seen that under TBM conditions, due to the high wear failure rate of the hob, the adverse effect of the acid solution on the cutter ring material is relatively small. When the pH is 5, the corrosion rate of the H13 steel sample is the lowest, which is 0.70g / (m 2 h). The reason why the corrosion rate of the H13 steel sample is low when immersed in the acidizing solution is that, on the one hand, the organic acid oxalic acid is less corrosive to the H13 steel sample; on the other hand, it is more because the foaming agent in the original solution component is an anionic surfactant, which will be closely attached to the surface of the cutter ring, so O2 is isolated, thus inhibiting oxygen absorption corrosion, which helps to reduce the corrosion effect of the acidizing agent on the cutter ring material; in order to ensure the weakening effect of the acidizing solution on the rock strength and take into account the inhibition of the corrosion of the acidizing solution on the rigid materials such as the hob and cutter disc, it is more preferred that the pH value of the acidizing solution is preferably 5.

[0091] The active lubrication method for a rolling cutter used in combination with a foaming agent of the present invention is characterized in that: Figure 3As shown, the foaming agent (32) is sprayed onto the tunnel face (4) through the spraying port (31) provided on the cutter head (3). The spraying port (31) provided on the TBM cutter head was previously mainly used to spray tap water onto the tunnel face (4) for the purpose of cooling and dust removal of the cutter head. It is worth noting that, unlike the aforementioned techniques of suppressing the degree of derivative development of the dense core at the bottom of the blade during the cutter penetration process by pre-grooving, rock breaking on the open face, and pre-irradiation weakening of the local rock mass, spraying the foaming agent (32), especially the acidizing solution, onto the entire tunnel face (4) can reduce the difficulty of tool penetration overall rather than locally, thereby reducing the wear rate of the cutter; in addition, since the integrity of the rock is reduced, the probability of derivative expansion of lateral cracks is increased, and the rock breaking efficiency is also improved.

[0092] like Figure 1 As shown, a performance testing method used in conjunction with a foaming agent of the present invention is characterized in that it includes the following steps:

[0093] S1: Prepare the original solution according to the geological conditions of the rock formation where the TBM is located. In this example, more specifically, whether the foam stabilizer needs to be mixed depends on whether it is in a deep and extremely hard rock formation, whether the chelating agent needs to be added depends on whether it is in a water-rich rock formation, and whether the lubricant needs to be added depends on whether it is in a highly abrasive rock formation such as quartzite.

[0094] S2: Conduct basic performance tests on the original solution, including the following steps:

[0095] S2-1: Foaming expansion ratio FER (%) calculated according to formula (1), which reflects the foaming performance of the foaming agent;

[0096] FER=V f / V t ×100% (9)

[0097] Where V f V is the foaming volume; t is the volume of the original solution;

[0098] S2-2: Calculate the defoaming rate F of the original solution according to formula (2) s The time t1 (min) taken to reach 50% is the foam half-life; this index reflects the ability of the foam to resist rupture under atmospheric pressure conditions;

[0099] F s =(M s / M0)×100% (10)

[0100] Where M s is the mass of the dissipated bubble; M0 is the initial mass of the bubble;

[0101] S2-3: Carry out observation of foam morphology quality; foam morphology quality is used to characterize the evolution characteristics of foam macroscopic and microscopic morphology at different times; more specifically, the fineness of the macroscopic foam is observed with the naked eye; at the same time, at a given magnification, an optical microscope is used to observe the diameter and distribution of the foam when the original solution is foamed (initial moment) and when the standing time is T1. In this case, more specifically, T1 is 30 minutes;

[0102] S3: Conduct stability test of the original solution, including the following steps:

[0103] S3-1 Pressure resistance test: refer to Figure 2 The schematic diagram of the pressure resistance test is shown in FIG. 1 , in which a pressure load F is applied to the original solution (2) prepared by S1 by means of a loading piston (1) to simulate the pressure level in the environment in which a foaming agent of the present invention is applied, that is, the stress level P0 of the knife-rock contact area; the pressure load F is calculated and determined using formula (3):

[0104] F=πr 2 P0 (11)

[0105] Where r is the radius of the loading piston (1); the stress level P0 in the knife-rock contact area is given by the following formula (4):

[0106]

[0107] Where C is a dimensionless coefficient, usually 2.12; R is the radius of the hob; σ c is the uniaxial compressive strength of rock; t is the tensile strength of the rock; T is the blade width of the roller cutter; S is the installation spacing of the roller cutters on the cutterhead, that is, the cutter spacing, which is generally 80mm; is the contact angle between the cutter and the rock, given by:

[0108]

[0109] Where H is the actual penetration depth of the hob in the project, which is generally 10 mm.

[0110] According to formula (6), the liquid precipitation ratio LPR (%) of the original solution from the initial moment to the static time T2 is measured; T2 is the time required for the original solution to completely precipitate; this index reflects the liquid discharge speed of the original solution within a given time under a given knife-rock contact zone stress level P0;

[0111] LPR=(V s / V0)×100% (14)

[0112] Where V s is the volume of liquid released due to foam bursting at time T2; V0 is the total liquid volume after the foam completely dissipates;

[0113] The foam half-life of the original solution under different pressure loads F (including the control group) was measured according to formula (15); in addition, the relative decrease ratio of the foam half-life under pressure load F (excluding the control group) relative to the foam half-life obtained in the control group, that is, the half-life decrease, was calculated; in this example, more specifically, the pressure load F was set to 0N (control group), 20N, 40N, 60N, 80N and 100N, and the measured results were Figure 4 and Figure 5 Test results shown.

[0114] S3-2 Acid, alkali and salt resistance test: Use HCl solution to adjust the pH value of the original solution to 1-6 to prepare different acid resistance test solutions; use NaOH solution to adjust the pH value of the original solution to 8-13 to prepare different alkali resistance test solutions; use NaCl solution to adjust the NaCl concentration in the original solution to 0.5wt%, 1wt%, 2wt%, 3wt%, respectively, to prepare different salt resistance test solutions; acid resistance test solution, alkali resistance test solution and salt resistance test solution are collectively referred to as test solutions; similar to S2: carry out basic performance test of test solution; in this example, more specifically, taking acid resistance test as an example, Figure 6 The above is a basic performance test result diagram of the original solution of a foaming agent of the present invention under different acidic pH value ranges, that is, different acid-resistant test solutions. In the figure, the decrease in foaming expansion ratio is the decrease ratio of the foaming expansion ratio of the acidified solution relative to the original solution at each pH value; the decrease in half-life is the decrease ratio of the half-life of the acidified solution relative to the original solution at each pH value. The test shows that the original solution of a foaming agent of the present invention has good acid, alkali and salt resistance, and can adapt to the acid, alkali and salt environment under the condition of water medium in ordinary rock formations.

[0115] Furthermore, a corrosion-resistant test sample having the same material as the cutter ring (such as H13 steel) is immersed in the test solution to carry out an electrochemical corrosion degree test, the steps of which are as follows:

[0116] ① The block H13 steel sample was ground and polished, and the sample was ultrasonically cleaned with ethanol and deionized water, and then dried to prepare the corrosion test sample; ② The corrosion test sample was completely immersed in the test solution (including a group of deionized water as a control group); ③ When the immersion time is T3: the open circuit potential of the corrosion test sample was measured; the electrochemical impedance spectroscopy of the corrosion test sample was analyzed by an electrochemical workstation to obtain the impedance data of the corrosion test sample in the test solution; the corrosion current density and corrosion potential were obtained by the anodic and cathodic polarization curve test; ④ The corrosion rate v′ of the corrosion test sample under different test conditions (such as different pH values ​​or different NaCl concentrations) was calculated using formula (7):

[0117]

[0118] Where: Δm is the mass difference of the corrosion test sample before and after immersion; A is the surface area of ​​the corrosion test sample;

[0119] In this example, more specifically, the soaking time T3 is 10 h;

[0120] S4: Conducting a grinding test of a cutter ring sample soaked in a foaming agent and a rock sample according to the present invention, including the following steps:

[0121] S4-1: soaking the rock sample in a foaming agent of the present invention;

[0122] S4-2: Fig.11 As shown, a grinding test of a cutter ring sample (7) and a rock sample (6) is carried out; preferably, during the grinding test: a three-axis force sensor is used to collect the vertical cutting load obtained by the cutter ring sample in real time; a high-speed camera is used to record the knife-rock grinding process at a frame rate of 60fps / s; a FLIR E6 infrared thermal imager (temperature measurement range is -20°C-250°C, and the measurement error is ±2%) is used to record the temperature field distribution on the surfaces of the cutter ring sample (7) and the rock sample (6);

[0123] S4-3: When the grinding distance is L: Use a precision electronic balance (measurement accuracy is ±0.001g) to measure the mass difference of the cutter ring sample before and after the grinding test, as well as the mass difference of the rock sample; Use the VHX-2000C ultra-depth three-dimensional digital microscope system to observe and record the surface profile morphology of the cutter ring sample and the rock sample; Record and calculate the slip rate of the cutter ring sample according to the authorized patent (2021106942459);

[0124] As a preferred method, in S4-2: based on the similarity principle of stress level P0 in the contact area between the cutter and the rock, when the actual penetration depth H of the hob in the project is 10 mm, refer to equations (4) and (5) to determine the test penetration depth h of the cutter ring specimen. x ; The linear cutting speed v of the cutter ring sample should be determined based on the principle of similar linear speed levels of the roller cutter breaking rock.

[0125] In this case, more specifically, Fig.10 As shown, on the basis of the planer (5), a knife-rock grinding test device (patent application number: 202011507895X) was built based on the similarity criterion; further, a knife ring sample (7)-rock sample (6) grinding test was carried out to verify the actual effect of a foaming agent of the present invention; in the figure, the knife ring sample (7) is arranged on the knife ring clamping device (52); the knife ring clamping device (52) is installed on the planer head (51); the key parameters of the grinding test are shown in Table 1.

[0126] Table 1 Key parameters of grinding test

[0127] Cutting data Numeric Grinding distance L 200mm Linear cutting speed v of knife ring specimen 0.18m / s <![CDATA[The test penetration depth h of the knife ring specimen x > 2mm

[0128] Grinding test process Fig.12 As shown. Fig.13 As shown, the theoretical slip rate and the measured slip rate of the knife ring sample (7) are respectively measured when the rock sample (6) is in dry conditions (dry cutting conditions), and when it is immersed in deionized water, original solution and acidified solution. As can be seen from the figure, by reasonably setting the mass fraction of each component of a foaming agent of the present invention, the relative friction coefficient of the knife and rock can be adjusted, thereby preventing the knife ring slip rate from fluctuating greatly after the application of the present invention. The regulating effect of some components on the relative friction coefficient of the knife and rock is reflected in:

[0129] 1) If Fig. 9 The figure shows the mean and increase data of the friction coefficient of the rock sample surface after being soaked in the acid solution with oxalic acid and citric acid as the acidifier. In the figure, OA3-6 has the same meaning as before; CA3-6 represents the acid solution with a pH value of 3-6 after acidification with citric acid. It can be seen from the figure that the acid molecules in the acidifier will chemically react with the mineral components in the rock, thereby increasing the roughness of the rock surface and improving the relative friction coefficient of the knife rock.

[0130] 2) Solvents, foaming agents and lubricants help to reduce the relative friction coefficient of knife-rock, and their friction reduction effects increase in sequence.

[0131] like Fig.14 As shown in the figure, the mass difference Δm of the cutter ring sample (7) before and after the grinding test when the rock is in a dry condition, and when it is soaked in deionized water, original solution and acidified solution; it can be seen from the figure that the wear rate of the cutter ring can be significantly reduced when soaked in a foaming agent of the present invention. Fig.15 As shown in the figure, the average depth and width of the grooves produced by the cutter ring sample (7) on the rock sample (6) after the knife-rock grinding test under the conditions of dry rock, deionized water, original solution and acidified solution immersion respectively; it can be seen from the figure that when oxalic acid is added as an acidifying agent to a foaming agent of the present invention, the rock breaking effect is significantly improved. Fig.16As shown, it is a curve showing the change of the mean value of the vertical cutting load on the cutter ring sample (7) with the time interval in the cutter-rock grinding test under the condition of the rock being in dry condition, and under the condition of being immersed in deionized water, original solution and acidified solution. As can be seen from the figure, a foaming agent of the present invention, especially the acidified solution after being acidified with oxalic acid, can effectively reduce the cutting load level of the cutter ring, thereby indirectly reducing the wear rate of the cutter ring. Based on the temperature field distribution on the surface of the cutter ring sample (7) and the rock sample (6), it can be seen that when the cutter ring sample (7) is in the above-mentioned wet cutting condition, the medium can effectively reduce the temperature of the contact interface between the cutter and the rock, which is also one of the reasons for the reduction of the wear rate of the cutter ring.

[0132] Based on the above results, combined with the surface profile morphology of the cutter ring sample and the rock sample obtained by observation, the following Fig.17 The schematic diagram of the mechanism of the effect of a foaming agent of the present invention on the knife rock is shown. Based on this figure, combined with the above test data and existing research results, it can be known that the mechanism of the effect of a foaming agent of the present invention on the knife rock is as follows:

[0133] 1) The acid molecules (82) in the foam component of the present invention undergo a series of chemical reactions with the rock mineral components as shown in Table 1, thereby destroying the integrity of the rock and weakening the physical and mechanical properties of the rock, thereby improving the digging ability of the rock; it is worth noting that when the active lubrication roller cutter method used in combination with the foam component of the present invention is used, that is, by spraying the foam component (32), especially the acidizing solution, on the entire face (4), the penetration difficulty of the cutter can be reduced overall rather than locally, and the wear rate of the roller cutter can be reduced; in addition, since the integrity of the rock is reduced, the probability of lateral cracks deriving and expanding is increased, and the rock breaking efficiency is also improved;

[0134] 2) The foaming agent of the present invention includes a foaming agent composed of anionic surfactants, wherein the active ingredient (81) not only closely adheres to the outer surface of the rock powder particles (8), thereby passivating the densified rock powder with sharp edges and corners, thereby reducing the high abrasiveness of the dense core, thereby fundamentally reducing the wear rate of the cutter ring; in addition, the active ingredient (81) forms a liquid film with a certain stability on the surface of the cutter ring sample (7), reducing the probability of direct contact between the cutter and the rock, and effectively avoiding the scratching and damage of the sharp edges and corners of the densified rock powder on the surface of the cutter ring.

[0135] 3) By spraying the foaming agent (32) on the entire face (4), the cutter ring sample (7) is placed under wet cutting conditions; at this time, the liquid medium flowing through the cutter-rock contact interface has a larger specific heat capacity and heat transfer efficiency than the air medium, so it can effectively reduce the surface temperature of the tool, take away more heat generated in the process of the hob breaking rock, and ultimately reduce the wear rate of the cutter ring.

[0136] 4) The liquid film can effectively isolate oxygen in the environment from contacting the surface of the cutter ring, thereby inhibiting oxygen absorption corrosion and unexpectedly reducing the corrosion effect of the acidifier on the cutter ring and other steel materials. When the organic acid oxalic acid is used as the acidifier, and the pH value of the acidified solution is controlled within a certain range, such as the preferred value of 5, the corrosion rate of the cutter ring material by the acidifier is much lower than the wear failure rate of the hob. The foaming agent of the present invention is environmentally friendly and easily degradable. These three reasons make it possible for the acidified solution configured by the present invention to be widely used in this field.

[0137] 5) As mentioned above, some components of a foaming agent of the present invention produce opposite positive and negative effects on the relative friction coefficient of the knife rock; by reasonably setting the mass fraction of the components, the relative friction coefficient of the knife rock can be adjusted, thereby preventing the knife ring slip rate from fluctuating significantly after the application of the present invention.

Claims

1. A foaming agent, characterized in that: Includes the original solution; The components and mass fractions of the original solution are as follows: Foaming agent: sodium lauryl ether sulfate sulfonic acid is used as the foaming agent; the mass fraction of the foaming agent is 15-32%; Foam stabilizer: silicone resin polyether emulsion is used as the foam stabilizer; the mass fraction of the foam stabilizer is 2%; Thickener: guar gum is used as thickener; the mass fraction of the thickener is 0.1-0.5%; Solvent: Deionized water was used as the solvent.

2. A foaming agent according to claim 1, characterized in that: The foam stabilizer is prepared by mixing silicone resin polyether emulsion and dodecyl dimethyl amine oxide; the mass fractions of silicone resin polyether emulsion and dodecyl dimethyl amine oxide are both 2%.

3. A foaming agent according to claim 1, characterized in that: The components of the original solution also include a chelating agent: Cublen-K2523 is used as the chelating agent, and its mass fraction is 1-1.5%.

4. A foaming agent according to claim 1, characterized in that: The original solution also includes lubricant: polyethylene oxide is used as lubricant, and its mass fraction is 0.1-6%.

5. A foaming agent according to claim 2, characterized in that: An acidulant is also included; the acidulant is used to acidify the original solution to obtain an acidified solution.

6. A foaming agent according to claim 5, characterized in that: Oxalic acid was selected as the acidifier.

7. A foaming agent according to claim 6, characterized in that: The pH value of the acidified solution was 5.

8. A method for actively lubricating a rolling cutter using a foaming agent according to any one of claims 1 to 7, characterized in that: The foaming agent is sprayed onto the palm face through the spraying port arranged on the cutter disc.

9. A performance testing method for a foaming agent according to any one of claims 1 to 7, characterized in that: The steps include: S1: Prepare the original solution according to the geological conditions of the rock formation where the TBM is located; S2: Conduct basic performance tests on the original solution, including the following steps: S2-1: Calculate the foaming expansion ratio FER (%) according to formula (1); FER=V f / V t ×100% (1) Where V f V is the foaming volume; t is the volume of the original solution; S2-2: Calculate the defoaming rate F of the original solution according to formula (2) s The time t1 (min) taken to reach 50% is the foam half-life; F s =(M s / M0)×100% (2) Where M s is the mass of the dissipated bubble; M0 is the initial mass of the bubble; S2-3: Carry out foam morphology and quality observation; S3: Conduct stability test of the original solution, including the following steps: S3-1 Pressure resistance test: A pressure load F is applied to the original solution prepared in S1 by means of a loading piston; the pressure load F is calculated and determined using formula (3): F=πr 2 P0 (3) Where r is the radius of the loading piston; P0 is the stress level in the knife-rock contact area, which is given by the following formula (4): Where C is the dimensionless coefficient; R is the radius of the hob; σ c is the uniaxial compressive strength of rock; t is the tensile strength of the rock; T is the blade width of the roller cutter; S is the distance between the cutters; is the contact angle between the cutter and the rock, given by: Where H is the actual penetration depth of the hob in the project; According to formula (6), the liquid precipitation ratio LPR (%) of the original solution from the initial moment to the static time T2 is measured; T2 is the time required for the original solution to completely precipitate; LPR=(V s / V0)×100% (6) Where V s is the volume of liquid released due to foam bursting at time T2; V0 is the total liquid volume after the foam completely dissipates; The foam half-life of the original solution under different pressure loads F was measured according to formula (7); In addition, the half-life reduction under pressure load F is calculated; S3-2 Acid, alkali and salt resistance test: prepare acid resistance test solution, alkali resistance test solution and salt resistance test solution; Conduct basic performance tests on the test solution; immerse the corrosion-resistant test sample with the same material as the knife ring in the test solution, conduct an electrochemical corrosion degree test, and measure the corrosion rate of the corrosion-resistant test sample; S4: Conduct a grinding test between the cutter ring sample and the rock sample soaked in the foam agent, and measure the mass difference of the cutter ring sample before and after the grinding test.

10. A performance testing method according to claim 9, characterized in that: S4 includes the following steps: S4-1: soaking the rock sample in the foaming agent; S4-2: Conduct a grinding test between the cutter ring sample and the rock sample; during the grinding test: use a three-axis force sensor to collect the vertical cutting load of the cutter ring sample in real time; use a high-speed camera to record the knife-rock grinding process; use an infrared thermal imager to record the temperature field distribution on the surface of the cutter ring sample and the rock sample; S4-3: When the grinding distance is L: weigh the mass difference of the cutter ring sample before and after the grinding test, and the mass difference of the rock sample; observe and record the surface profile morphology of the cutter ring sample and the rock sample; calculate the slip rate of the cutter ring sample.